Comparative Intraoperative and Postoperative Outcomes of Undergoing CT-Guided Coeliac Plexus Blockade and Coeliac Plexus Neurolysis in Patients with Intra-Abdominal Malignancies - Muhammad Ramzan, Muhammad Usman Younas, Asim Ali, Khoala Riaz, Abdullah Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare intraoperative and postoperative outcomes of CT-guided coeliac plexus blockade (CPB) and/or coeliac plexus neurolysis (CPN) in patients with intra-abdominal malignancies. Methods: Retrospective single-centre study in Radiology Department of PKLI & RC Lahore of consecutive patients treated between June 2022 and May 2023. Eighty patients with intra-abdominal malignancy-related abdominal pain who underwent 110 procedures (32 CPB, 78 CPN) were included. Baseline characteristics, malignancy type, procedural details, Numeric Rating Scale (NRS 0–10) pain scores (pre-procedure, 1 week, 1 month, 3 months), breakthrough cancer pain (BTcP) frequency, opioid consumption, adverse events and survival after CPN were recorded. Results: Eighty patients (mean age 58.4 ± 9.7 years; 47 male) underwent 110 image-guided procedures. Mean NRS decreased to 3.1 ± 1.4 at 1 week (mean reduction −5.3; p < 0.001), 2.8 ± 1.3 at 1 month and 3.5 ± 1.8 at 3 months. Patients receiving repeated CPN had greater cumulative pain reduction (mean NRS change 6.1 vs 4.9; p = 0.02). Higher baseline pain intensity was associated with larger absolute pain reduction. Time from diagnosis to CPN was shorter in pancreatic cancer compared with other intra-abdominal malignancies. After CPN, 58% of patients had stable or reduced analgesic medication; 16% reported pain during the procedure. Conclusions: CT-guided CPN is a safe, effective intervention for background cancer-related abdominal pain and BTcP in patients with intra-abdominal malignancy, providing clinically meaningful and often durable pain relief, opioid sparing in a substantial proportion, and a low major complication rate. Keywords: coeliac plexus neurolysis; coeliac plexus block; CT-guided; cancer pain; pancreatic cancer; interventional radiology.